VOLUNTEERING ACTIVITIES AS MEANS OF FORMATION OF SOCIO-ECOLOGICAL CONSCIOUSNESS OF STUDENTS - L. S. Aygubov; K. I. Khadzhialiev (Юг России: экология, развитие, 2017)
Aim. The aim is to analyze the current state of social and ecological consciousness of youth and consider the introduction of student volunteering activity in the formation of ecological consciousness in the context of Republic of Dagestan.Discussion. The social and environmental issues with a negative shade are largely typical for Dagestan. The consequences of these are one of the areas of social work the main goal of which is to provide assistance and support to people who are in difficult life situation. Annually, more than 150 bachelors and masters of social work graduate the Department of Sociology of Dagestan State University. Proper use of the potential of student volunteering activities, in our opinion, will help to a certain extent to solve the existing in the country social and environmental problems, reduce their negative impact on the population.Conclusion. The Republic of Dagestan is a very important region for the realization of the ideas of volunteerism. However, an analysis of the work done has shown that voluntary associations, as a rule, exist in many universities and their activities is a mere formality as they are similar to circles of interest. There is a lack of systematic and purposeful approach on the use of voluntary activities of students. We came to the conclusion that it is crucial to implement an appropriate approach, the main objectives of which shall be as follows: the organization of training aimed at the development of social activity and personal potential; formation of ecological awareness; use of volunteering activities of future social workers in dealing with social and environmental problems.